Two-year postnatal outcome of 263 cases of fetal ventriculomegaly. (2nd May 2020) - Kumar, Manisha; Garg, Nikita; Hasija, Aayushi; Pritam, Anuja; Shukla, Priyanka; Vanamail, Perumal; Roy Choudhury, Subhasis
Abstract: Objectives: To find out the outcome of fetal ventriculomegaly (VM) in terms of survival at birth and after two years and to evaluate the antenatal factors which influence the postnatal outcome. Method: We performed a 10-year prospective, observational study (2008–2018) including all prenatally detected fetal VM. Two years follow up of all live born was done to observe their survival, physical morbidity, and developmental delay. Results: Fetal VM was seen in 263/648 (40.6%) cases with central nervous system malformation. VM was severe in 85.9% and was associated with other anomalies in 56.3% of the cases. Total 40.3% cases with VM were live born. The outcome at birth and was poorest with severe VM (40.7%) and when VM was associated with multiple defects (30%). Only 23.6% survived beyond two years of age. There was developmental delay in 24.2% cases. Logistic regression showed that, the presence of associated defect and severe VM were significant poor prognostic factors for survival at birth ( p = .001) and after two years of age ( p = .002). Conclusions: In a low resource setup the problems associated with fetal VM were compounded by late referral. The knowledge of the outcome in existing setup provides data for realistic counselling to the couple.